1.45 GPa ultrastrong cryogenic strength with superior impact toughness in the in-situ nano oxide reinforced CrMnFeCoNi high-entropy alloy matrix nanocomposite manufactured by laser powder bed fusion. (20th January 2022) - Kim, Young-Kyun; Kim, Min-Chul; Lee, Kee-Ahn
Abstract: CrMnFeCoNi high-entropy alloys (HEAs) exhibit an excellent combination of tensile strength and ductility at cryogenic temperatures. This study led to the introduction of a new method for the development of high-performance CrMnFeCoNi HEAs at cryogenic temperatures by jointly utilizing additive manufacturing (AM) and the addition of interstitial atoms. The interstitial oxygen present in the powder feedstock was transformed into beneficial nano-sized oxides during AM processing. The HEA nanocomposite fabricated using laser powder bed fusion (L-PBF) not only contains heterogeneous grains and substructures but also a high number density of nano-sized oxides. The tensile results revealed that the L-PBF HEA nanocomposite has superior yield strengths of 0.77 GPa and 1.15 GPa, and tensile strengths of 0.92 GPa and 1.45 GPa at 298 K and 77 K, respectively. In addition, the Charpy impact energies of the samples tested at 298 K and 77 K were measured as 176.2 J and 103.7 J, respectively. These results indicate that the L-PBF HEA nanocomposite successfully overcomes the well-known strength-toughness trade-off. The tensile deformation microstructure contained a relatively large number of deformation twins (DTs) at cryogenic temperature, a possible consequence of the decrease in the stacking fault energy with decreasing temperature. On the other hand, cracks were found to propagate along the grain boundaries at room temperature, whereas a transgranular crack was observed at cryogenic temperature in the specimens fractured as a result of the Charpy impact. Highlights: In-situ oxide reinforced crmnfeconi HEA was manufactured by selective laser melting. HEA nanocomposite reveals heterogeneous grain structure, nano-size in-situ oxide, and dislocation network induced-substructure. HEA nanocomposite has cryogenic tensile strength of 1.45 GPa with elongation of 23.4%, while also showing cryogenic impact toughness of 103.7 J.